PALM OIL FARMERS’ PERCEPTIONS OF PRICE FLUCTUATIONS IN FRESH FRUIT BUNCHES (FFB) IN TURANGI VILLAGE, SALAPIAN SUBDISTRICT, LANGKAT REGENCY - Putriani Napitupulu; Rio Prayogi; Myrna Pratiwi Nasution (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2026)
Small-scale oil palm farmers are highly vulnerable financially because the price of fresh fruit bunches (FFB) can fluctuate within a matter of weeks. The objective of this study is to examine how the income of oil palm farmers in Turangi Village is affected by changes in FFB prices. This quantitative study involved 100 respondents, determined using the Slovin formula. A Likert-scale questionnaire was used to collect data, while analysis was conducted using simple linear regression and Spearman’s rank correlation test. The results of the Spearman’s correlation test indicate a fairly strong and significant positive relationship, with an rs value of 0.472 and a significance level of 0.002 < 0.05. Price changes have a significant impact on income, based on the results of simple linear regression, which showed a t-value of 3.263 > the critical t-value of 1.996 with a significance level of 0.002 < 0.05. Price changes explain only 9.8% of the variation in income, while other factors outside the model account for 90.2%, based on an R value of 0.313 and an R² of 0.098. These findings confirm that price fluctuations have a significant relationship with and influence on farmers’ income. To improve the model’s ability to explain changes in farmers’ income, it is recommended to conduct further research by incorporating additional factors such as land area, production costs, and productivity.